Association of depression with body mass index classification, metabolic disease, and lifestyle: A web-based survey involving 11, 876 Japanese people. (July 2018) - Hidese, Shinsuke; Asano, Shinya; Saito, Kenji; Sasayama, Daimei; Kunugi, Hiroshi
Abstract: Body mass index (BMI) and lifestyle-related physical illnesses have been implicated in the pathology of depression. We aimed to investigate the association of depression wih BMI classification (i.e., underweight, normal, overweight, and obese), metabolic disease, and lifestyle using a web-based survey in a large cohort. Participants were 1000 individuals who have had depression (mean age: 41.4 ± 12.3 years, 501 men) and 10, 876 population-based controls (45.1 ± 13.6 years, 5691 men). The six-item Kessler scale (K6) test was used as a psychological distress scale. Compared to in the controls, obesity and hyperlipidemia were more common and frequency of a snack or night meal consumption was higher, whereas frequencies of breakfast consumption and vigorous and moderate physical activities were lower in the patients. K6 test scores were higher for underweight or obese people compared to normal or overweight people. A logistic regression analysis showed that the K6 test cut-off score was positively associated with being underweight, hyperlipidemia, and the frequency of a snack or night meal consumption, whereas it was negatively associated with the frequency of breakfast consumption in the patients. Logistic regression analyses showed that self-reported depression was positively associated with metabolic diseases and the frequency of a snack or night meal consumption, whereas it was negatively associated with the frequency of breakfast consumption. The observed associations of depression with BMI classification, metabolic disease, and lifestyle suggest that lifestyle and related physical conditions are involved in at least a portion of depressive disorders. Highlights: Six-item Kessler scale (K6) score was higher in underweight and obese people. K6 cut-off score was associated with hyperlipidemia and extra meals in patients. K6 cut-off score was negatively associated with breakfast. Self-reported depression was associated with metabolic diseases and extra meals. Self-reported depression was negatively associated with breakfast.